Establishment of a Sensitive qPCR Methodology for Detection of the Olive-Infecting Viruses in Portuguese and Tunisian Orchards - Campos, Maria Doroteia; Zellama, Mohamed Salem; Varanda, Carla; Materatski, Patrick; Peixe, Augusto; Chaouachi, Maher; Félix, Maria do Rosário (Frontiers in Plant Science, 2019)
Sensitive detection of viruses in olive orchards is actually of main importance since these pathogenic agents cannot be treated, their dissemination is quite easy, and they can have eventual negative effects on olive oil quality. The work presented here describes the development and application of a new SYBR®Green-based real-time quantitative PCR (qPCR) analysis for specific and reliable quantification of highly spread olive tree viruses: Olive latent virus 1 (OLV-1), Tobacco necrosis virus D (TNV-D), Olive mild mosaic virus (OMMV), and Olive leaf yellowing-associated virus (OLYaV). qPCR methodology revealed high specificity and sensitivity, estimated in the range of 0.8-8 copies of the virus genome, for the studied viruses. For validation of the method, total RNA and double strand RNA (dsRNA) from naturally infected trees were used. In a first trial, dsRNAs from trees of cv. ‘Galega vulgar’ from a Portuguese orchard, were subjected to qPCR and from the 30 samples tested, 26 were TNV-D and/or OMMV-positive and 25 were OLV-1 positive. In a second trial, total RNA from trees of different cultivars from Tunisian orchards, were here tested by qPCR and all viruses were detected. From the 33 samples studied, the most prevalent virus detected in Tunisia orchards was OLV-1 (31 samples diagnosed), followed by OLYaV (20 samples diagnosed), and finally the combination in last TNV-D and/or OMMV (12 samples diagnosed). In both trials, qPCR demonstrated to be effective and sensitive, even when using total RNA as template. qPCR through the use of a SYBR®Green methodology enabled, for the first time, a reliable, sensitive and reproducible estimation of virus accumulation in infected olive trees, in which viruses are usually in low titres, that will allow gaining new insights in virus biology essential for disease control and give an important contribution for establishment of sanitary certification of olive propagative material